2021
DOI: 10.1021/acs.langmuir.0c03238
|View full text |Cite
|
Sign up to set email alerts
|

Selective Bonding Effect of Heterologous Oxygen Vacancies in Z-Scheme Cu2O/SrFe0.5Ta0.5O3 Heterojunctions for Constructing Efficient Interfacial Charge-Transfer Channels and Enhancing Photocatalytic NO Removal Performances

Abstract: An interfacial structure is crucial to the photoinduced electron transport for a heterostructure photocatalyst. Constructing an interfacial electron channel with an optimized interfacial structure can efficiently improve the electron-transfer efficiency. Herein, the rapid electron-transfer channels were built up in a Cu2O/SrFe0.5Ta0.5O3 heterojunction (Cu2O/SFTO) based on the selective bonding effect of heterologous surface oxygen vacancies in the SFTO component. The heterologous surface oxygen vacancies, name… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…An S-scheme heterojunction is composed of reduction photocatalysts (RP) and oxidation photocatalysts (OP) with direct and intimate contact, staggered band structure, and a distinct charge-transfer route, maintaining a strong redox potential for photocatalysis. In the past few years, numerous efforts have been devoted to constructing S-scheme heterojunctions for CO 2 photoreduction, and it was found that high interface transfer resistance is a bottleneck for their applications in photocatalysis. ,, …”
Section: How the Defects Matter For Co2 Photoreductionmentioning
confidence: 99%
See 3 more Smart Citations
“…An S-scheme heterojunction is composed of reduction photocatalysts (RP) and oxidation photocatalysts (OP) with direct and intimate contact, staggered band structure, and a distinct charge-transfer route, maintaining a strong redox potential for photocatalysis. In the past few years, numerous efforts have been devoted to constructing S-scheme heterojunctions for CO 2 photoreduction, and it was found that high interface transfer resistance is a bottleneck for their applications in photocatalysis. ,, …”
Section: How the Defects Matter For Co2 Photoreductionmentioning
confidence: 99%
“…Numerous efforts have been made to construct heterojunctions to boost CO 2 photoreduction (see the related review 4 ); however, the photocatalytic activity of existing heterojunctions is unsatisfactory, mainly due to their low interfacial charge transfer efficiency as well as sluggish surface reaction kinetics. 2,5,6 Structure defects, such as point defects (cation or anion vacancies), line defects (dislocations), facet defects (grain boundaries), and volume defects (holes), are common in prepared materials, while their contents are too low to have an effect on photocatalysis. When abundant defects, such as the most common anion vacancies, are created on the surfaces of semiconductors, their great potential on boosting photocatalysis emerges.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, LaCrO 3 –NaTaO 3 solid solutions have performed improved photocatalytic reactions with an enhanced electron population due to a charge compensation mechanism that sensitizes the tantalate to visible light . Similarly, BiFeO 3 , NaNbO 3 , KNbO 3 , KTaO 3 , NaTaO 3 , and other tantalate-based heterostructures have been synthesized and showed benefits compared to their bulk parts.…”
Section: Introductionmentioning
confidence: 99%